Fifth Amendment Compelled Statements: Modeling the Contours of Their Protected Scope - Kate E. Bloch (Washington University Law Quarterly, 1994)
If there is a principled framework that explains the current doctrine treating compelled statements, the first step in evaluating that treatment is to unearth and articulate the framework. The primary focus of this Article is to initiate that step. Once unearthed, a framework provides a common language and a motivation for courts to explain their reasoning in arriving at disparate levels of protection. Clearer explanations improve dialogue and understanding, both within and without the courts.
Keywords: Self-incrimination